PARTIAL LIST AVIFAUNA SEIZED BY REGIONAL OFFICE OF SANTA MARIA IBAMA-RS - Felker, Roselene Marostega; Dörr, Andréa Cristina; Rovedder, Ana Paula; Piazza, Eliara Marin; Dick, Grasiele (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708734 Brazilian birdlife is among the most diverse in the world and also among the most trafficked. Against this backdrop, this paper aims to carry out survey of birds seized by the Regional Office of IBAMA Santa Maria, during the periods 2006, 2007 and 2008, through deficiency notices issued by environmental analysts. It was observed in the survey of 1250 individuals apprehension in different regions of the state. Among these, Paroaria coronata, was the species most individuals seized, followed by Sicalis flaveola and Cyanocompsa brissonii. The family with the largest number of representatives was seized Emberizidae, then the Psittacidae, and Santa Maria, the city with the largest number of notices of infractions against the avifauna recorded in this survey. Considering that most birds have learned how domestication final destination, it is necessary to raise awareness of the population, so there is no support of such trafficking, involving the Brazilian fauna.